Membongkar di sebalik misteri MH370 - Mohammad Qayyum A. Abadaruddin ([Kajang, Selangor] : Casamas Resources Sdn. Bhd., 2014)
On history and chronology of Malaysian plane crash MH370.
Includes bibliographical references (pages 223-224).
Keywords: Malaysia Airlines Flight 370 Crash, Indian Ocean, 2014.; Aircraft accidents -- Indian Ocean; Aircraft accidents -- Investigation -- Indian Ocean; Aircraft accidents -- Malaysia